On the Evolution of Wireless Communication Technologies and Spectrum Sharing for Public Safety: Policies and Practice. Issue 3 (September 2016) - Kapucu, Naim; Haupt, Brittany; Yuksel, Murat; Guvenc, Ismail; Saad, Walid
Abstract : The field of emergency and crisis management continuously strives to enhance collaboration, communication, and coordination among public safety organizations. Successful integration is challenging due to current policies and regulations. Moreover, policymakers must predict future needs. Regardless of the challenges, development and growth of a national public safety communication system is no longer a hopeless cause and is anticipated to mitigate challenges by enhancing security, dependability and fault tolerance, cost effectiveness, interoperability, spectral efficiency, and advanced capabilities. Although this national public safety communication system is in the process of being implemented by various local, state, and federal agencies, such adoption is voluntary and attributes to a disconnect between policies and stakeholders. This study reviews the evolution of public safety communication system and discusses benefits and challenges of a national system, the policies and regulations affecting wireless communication technologies and spectrum sharing, and the influence of evolving technologies.